2018
DOI: 10.1093/eurheartj/ehy066
|View full text |Cite|
|
Sign up to set email alerts
|

Antithrombotic therapy and body mass: an expert position paper of the ESC Working Group on Thrombosis

Abstract: Increasing prevalence of cardiovascular disease and new evidence on the effects of antithrombotic therapies have expanded the use of antiplatelet and anticoagulant drugs. In addition, extremely low and high body weights have become more common due to frailty associated with ageing and to the global epidemic of obesity, 'globesity', respectively. These extreme body weights affect cardiovascular risk, including mortality, as well as the pharmacokinetics and safety profiles of antithrombotic drugs, some of which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
90
0
16

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 223 publications
(241 reference statements)
7
90
0
16
Order By: Relevance
“…Our findings of a trend towards worse prognostics in patients who are obese underlines the importance of more patient-centred care [38], in particular with respect to choosing the appropriate anticoagulant therapy for each individual patient. In this way, we can confirm the call for increased awareness on dedicated prophylactic and therapeutic anticoagulant regimens in obesity [7]. Reassuringly, a recent well-sized cohort study suggested similar efficacy and safety between direct oral anti-Xa inhibitors and warfarin in patients who are morbidly obese, although these retrospective findings warrant confirmation in prospective studies [39].…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Our findings of a trend towards worse prognostics in patients who are obese underlines the importance of more patient-centred care [38], in particular with respect to choosing the appropriate anticoagulant therapy for each individual patient. In this way, we can confirm the call for increased awareness on dedicated prophylactic and therapeutic anticoagulant regimens in obesity [7]. Reassuringly, a recent well-sized cohort study suggested similar efficacy and safety between direct oral anti-Xa inhibitors and warfarin in patients who are morbidly obese, although these retrospective findings warrant confirmation in prospective studies [39].…”
Section: Discussionmentioning
confidence: 53%
“…Regarding treatment, it is debated whether the patients at extremes in body weight should receive modified treatment regimens [7]. Because of limited clinical data available for patients who are obese, the International Society on Thrombosis and Haemostasis (ISTH) guidance document advises against the use of direct oral anticoagulants in patients with a body weight higher than 120 kg or a BMI higher than 40 [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese adipose tissue amplifies the secretion of proinflammatory cytokines and chemokines, leading to platelet activation. 39 Intensive antithrombotic therapy may be effective for young patients with greater body weight; however, adjustment of drug doses based on body weight remains controversial with regard to bleeding risk due to overdose. 39 Further detailed analysis is necessary to assess the factors affecting PL18-AUC10 during PPCI.…”
Section: Discussionmentioning
confidence: 99%
“…A similar indication comes from the 2018 position paper of ESC Working group, that suggests a full standard dose of NOACs in patients with normal/grade I obesity (BMI <35 kg/m 2 ), with no/insufficient data for apixaban, edoxaban and dabigatran for obesity class II-III; conversely Rivaroxaban full dose can be administered with caution in patients with class II obesity (BMI 35-39.9 kg/m 2 ) 30 .…”
Section: A N U S C R I P Tmentioning
confidence: 98%